Modeling of convective drying kinetics of Pistachio kernels in a fixed bed drying system - Balbay, Asim; Sahin, Omer; Ulker, Hakan (National Library of Serbia, 2013)
Drying kinetics of Pistachio kernels (PKs) with initial moisture content of 32.4% (w.b) was investigated as a function of drying conditions in a fixed bed drying system. The drying experiments were carried out at different temperatures of drying air (40, 60 and 80?C) and air velocities (0.05, 0.075 and 0.1 m/s). Several experiments were performed in terms of mass of PKs (15g and 30g) using a constant air velocity of 0.075 m/s. The fit quality of models was evaluated using the determination coefficient (R2), sum square error (SSE) and root mean square error (RMSE). Among the selected models, the Midilli et al model was found to be the best models for describing the drying behavior of PKs. The activation energies were calculated as 29.2 kJ/mol and effective diffusivity values were calculated between 1.38 and 4.94x10-10 m2/s depending on air temperatures.
Keywords: activation energy; mathematical modeling; drying; unshelled pistachio